THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CLIMATE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS A MEDIATING VARIABLE (STUDY OF PROBOLINGGO REGENCY MANPOWER SERVICE EMPLOYEES) - Chyntia Putri Alifah Baskoro; Margono; Nanang Suryadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The Influence of Transformational Leadership and Organizational Climate on Employee Performance with Organizational Citizenship Behavior as a Mediating Variable (Study of Probolinggo Regency Manpower Service Employees). This research was conducted at the Probolinggo Regency Manpower Office. The population used in this research was all permanent employees of the Probolinggo Regency Manpower Service, totaling 55 people. The sample in this study was aimed at permanent employees of the Probolinggo Regency Manpower Service. Then the sample size in this study was not large, so the author took the entire population, namely 55 permanent employees of the Probolinggo Regency Manpower Service to get a better level of accuracy.